Entwurfsoptimierung von selbst-adaptiven Wartungsmechanismen für software-intensive technische Systeme - Märtin, Lukas (The Karlsruhe Series on Software Design and Quality / Ed. by Prof. Dr. Ralf Reussner, 2018)
This work presents novel concepts for efficient decision support in reconfiguring software-intensive technical systems with limited maintenance access. In contrast to purely redundancy-oriented approaches, the proposed methodology is based on the predictive pre-calculation of adequate configuration alternatives in the relevant design space. The knowledge about configuration relationships is manifested early and used for the autonomic cost-efficient assessment of configuration alternatives.